Multifunctional devices based on induced polar states - Kosorotov, V.F.; Shchedrina, L.V.; Levash, L.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Search for new pyroactive effective materials with controlled polarization properties is carried out with the goal of developing the new generation of pyroelectric sensors with extended functional capabilities. Elaborated multifunctional pyroelectric device – watt-joulemeter combines the functions of the meter of radiation power and that of radiation energy. Proposed technology based on a consideration of the electric potential spatial distribution in piezoelectric crystals under the inhomogeneous heating conditions provides the needed requirements for a formation of two measuring channels on the common sensitive element. Electronic treatment of output signals provides a simultaneous measurement of the power and energy of radiation pulses.